Integrating Pancasila Values and Islamic Culture: Developing An Instructional Module For Character Strengthening in Islamic Elementary Schools - Abu Dharin; Muhammad Anas Ma’arif; M. Ajib Hermawan; Yuslam Yuslam; Agam Anantama; Syukrul Hamdi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
The integration of national character development with Islamic cultural values is a crucial issue for Islamic elementary schools as they implement the government-mandated Pancasila Student Profile Strengthening Project (P5). This study aimed to develop a P5 module integrated with Islamic culture and evaluate its validity, practicality, and effectiveness for use in Islamic elementary school learning. The research employed a Research and Development (R&D) approach, following the systematic stages of the Dick & Carey instructional design model. Data were gathered through observation, interviews, documentation, questionnaires, and formative tests, with module feasibility assessed via expert validation and practicality examined through teacher and student classroom trials. Effectiveness was determined using Aiken’s formula and paired sample t-tests. The findings indicate that the developed module is highly feasible for implementation, requiring only minor revisions to illustrations and sentence clarity. Furthermore, the module was proven practical in classroom settings and effective in significantly improving students’ mastery of the Pancasila Student Profile. This research implies that integrating Islamic culture into the P5 framework offers a contextual and meaningful approach to character education, providing a valuable learning resource for Islamic educational institutions in strengthening student character with both national and religious values.